Earthquake Resistant House Building Structure - Ardiansyah Ardiansyah (Bandar Lampung University (UBL), 2012)
Earthquakes are unpredictable when it comes so anticipation is needed as early as possible. One way to anticipate earthquakes is to design buildings or houses that are resistant to earthquakes. After a small earthquake, the building must still be able to fully functional within a short time and repairing costs are not expensive. After a medium earthquake, the building can function again after repairing and strengthening of the main parts of the structure is completed. Meanwhile, after a major earthquake, the building may no longer can be used but the occupants of the building can be saved and the items inside the building can be protected. Any additional security value of a house requires adequate additional cost. Security value is not simply a house that is free from thieves, but natural disturbances such as floods, earthquakes, tsunamis, hurricanes and others. But all of those values are fair price for the security and comfort.